A review of Minilimosina Roháček (Diptera: Sphaeroceridae) from China - Su, Lixin; Liu, Guangchun; Xu, Jie (Zootaxa, 2015)
A review of the genus Minilimosina Roháček, 1983 of China, comprising 16 species, is given, with data about types, published descriptions and figures, and distributions. A key to the Chinese species of the genus Minilimosina is provided and three new species are described and illustrated: M. gracilenta Su sp. nov., M. parafanta Su sp. nov. and M. tapiehella Su sp. nov.. The male of M. archboldi Marshall, 1985 is redescribed. Females of M. luteola Su, 2011 and M. cornigera Roháček & Marshall, 1988 are described and illustrated for the first time. Phylogenetic relationships of M. cerciseta Su, 2011, M. luteola Su, 2011, M. obtusispina Su, 2013, M. quadrispinosa Su, 2011, M. gracilenta Su sp. nov., M. parafanta Su sp. nov. and M. tapiehella Su sp. nov. are discussed.